(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Construction industry is one of the fastest growing compared to other industries. The development of any country basically needs an infrastructure which could sustain for long time. The infrastructure development leads to the development of the construction engineering. In the construction industries, now days the management has played the vital role for completion of the project during specified time and with minimum possible losses. The construction management has become very popular and has opened new doors of the opportunities for the management students all over the world. The construction industries are passing through the transition phase. Previously most of the systems were human dependent but now the processes are simplified with the help of the technology. Authors have tried to present an overview of the scenario of construction industries over the recent years and also discussed the upcoming technologies in the field of the construction industries.